Relationship between knowledge and treatment satisfaction with psychological well-being among haemodialysis patients: a single center study - Erandika, Naduni H. G.; Gunarathne, Nadeeka S.; Nayanamali, Ayesha; Muthukuda, Priyanthi S.; Nanayakkara, Nishantha (International Journal of Research in Medical Sciences, 2022)
Background: Haemodialysis (HD) patients are subjected to bio-psychosocial stress in many ways even after successful hemodialysis session. Therefore, this study was designed to survey on relationship between knowledge and treatment satisfaction with psychological well-being among haemodialysis patients. Methods: This cross-sectional study included 100 HD patients who were referred to emergency dialysis unit, nephrology and transplant unit, National Hospital, Kandy during the year 2019. Data were collected using a self-administered questionnaire. Results: Mean age of this study group was 45.17 (13.6) years; two dominant etiologies of chronic renal failure were diabetic nephropathy and hypertension accounting for nearly 61% of the study population. Only 19% of patients presented with emotional suffering and 40% of patients worried about their disease condition. However, majority of the patients satisfied with nursing care and nurses’ co-operation while they are on HD treatment. Moreover, they confirmed nurses’ co-operation helped to reduce their stress level. Further, knowledge on HD compliance (p=0.000), satisfaction on nursing staff attitudes (p=0.001), satisfaction on nursing staff concern about the health issues (p=0.001) and worrying about the kidney disease condition (p=0.000) had statistically significant association with mental stress in this study cohort. Conclusions: The topic of stressors is very important among patients receiving dialysis, as these affect their psycho-social and physiological wellbeing. Thus, health care team is playing an important role in providing patients with effective psycho-social and physiological support.